Estudo sobre a ecologia dos flebótomos do Parque Nacional da Serra dos Órgãos, Estado do Rio de Janeiro (Diptera : Psychodidae, Phlebotominae) - Aguiar, Gustavo Marins de (1984)
Systematic study on aspects of the ecology of sandflies at the Serra dos orgãos National Park, a mountainous forested area in the State of Rio de Janeiro. A total of 7554 specimens from 20 distinct species, - including a new one (Lutzomyia sp.1) were collected. In captures with human bait Lutzomyia ayrozai and L. hirsuta represented 92% of the total specimens. Both were frequent during the whole year, but became predominant in different periods: the former in Summer and the latter during Winter. They fed on blood in larger numbers at different times of the day: L. hirsuta between 6:00 and 10:00 P. M. and L. ayrozai from 11:00 P.M. to 2:00 A.M. In regard to vertical distribution in the forest, as far as sandflies are concerned – L. fischeri showed the highest degree of acrodendrophily, followed far behind by L. sp.1; L. shannoni was eclectic; nearly all specimens of L.hirsuta. were caught on persons or animals on the ground, while L.pessoai, L. ayrozai, L.davisi, L. sp.2, L.microps and L.monticola fed e eclusively at ground level. L. barrettoi, which did not occur on human bait, was the most abundant species in light traps. Except for L. shannoni, all local species exhibited a considerable preference for dark nights, during new moon and were most scarce in clear nights, during full moon, both in captures with human bait or with light traps.